2013
DOI: 10.1177/0886260513507140
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Intimate Partner Violence Against Women on Under-Five Child Mortality in Bangladesh

Abstract: It is well established that intimate partner violence (IPV) against women adversely affects maternal morbidity and mortality. But a limited number of studies were found in the literature regarding the association between IPV and under-five child mortality. In this article, using Bangladesh Demographic and Health Survey (BDHS) 2007 data, we examined the effect of IPV on under-five child mortality. A product-limit approach was used for bivariate survival analysis, and Cox proportional hazard multiple regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Study findings provide evidence for an association showing that children born to women who are IPV survivors were significantly more likely to die as newborns, infants, and children under five. These findings are consistent with those of previous studies in Bangladesh [16], India [17], and Kenya, Egypt, Malawi, Honduras, & Rwanda [18]. In essence, we concur that the high infant and child mortality rates among women experiencing IPV could be influenced by the negative impact on their mental and physical health, which is likely to affect their pregnancy and subsequent caregiving [19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Study findings provide evidence for an association showing that children born to women who are IPV survivors were significantly more likely to die as newborns, infants, and children under five. These findings are consistent with those of previous studies in Bangladesh [16], India [17], and Kenya, Egypt, Malawi, Honduras, & Rwanda [18]. In essence, we concur that the high infant and child mortality rates among women experiencing IPV could be influenced by the negative impact on their mental and physical health, which is likely to affect their pregnancy and subsequent caregiving [19].…”
Section: Discussionsupporting
confidence: 92%
“…IPV affects the social, mental, and psychological well-being of the mother due to the traumatic nature of the violence they experience. This, therefore, affects their capacity to care for their child and contributes to underutilization of maternal health services [16]. Given the role that mothers play in a child's life, their health status during and after pregnancy is a direct predictor of an infant and child's health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also consistent evidence that due to inevitable changes in physical, social, emotional, and economic needs, women are uniquely vulnerable to IPV victimization during pregnancy, and that women victims of IPV during pregnancy are more likely to experience repeated and severe forms of IPV, which places the health of mothers ad their unborn children at great risk [5,6]. Specifically, a vast body of research has shown that IPV during gestation is a significant risk factor for a variety of negative prenatal and postnatal outcomes including low-quality prenatal care [7,8], low fetal growth, low birth weight, adverse birth outcomes, and infant hospitalization [9][10][11][12][13], infant and child malnutrition and mortality [14][15][16][17], inadequate immunization during infancy [18], infant physical abuse, asthma onset during childhood and adolescence [19][20][21] and post-traumatic stress disorder (PTSD) symptoms during infancy and childhood [22,23].…”
Section: Empirical Evidence On Childhood Exposure To Ipvmentioning
confidence: 99%
“…It has been found in many studies that there exists a negative impact of IPV on maternal physical and mental health [18][19][20] . Consequently, this negative impact of IPV on women may directly or indirectly affect children.…”
Section: Introductionmentioning
confidence: 99%